A discipline-specific pedagogical professional development graduate program fosters development of integrated scholars: an evaluation of the Future Undergraduate Science Educators (FUSE) program - Marina L. Ellefson; Mona M. Monfared (Journal of Microbiology & Biology Education)
ABSTRACT Here, we present a model for a decentralized, discipline-specific pedagogical professional development program for STEM PhD students interested in teaching and learning careers in higher education. The FUSE (Future Undergraduate Science Educators) program at UC Davis follows the structure of the University of California’s Graduate Academic Certificate. FUSE scholars take 12 units of coursework, which span a variety of teaching-related topics, such as an introduction to Scientific Teaching, teaching portfolio development, and an authentic mentored teaching experience. By providing formal training in Scientific Teaching and offering a mentored teaching practicum, FUSE aims to decrease the time it takes between attaining a PhD and getting a teaching position. The FUSE program is unique in that it offers decentralized pedagogical training within the same academic unit in which students receive their research training. This positioning of FUSE has the potential to affect cultural change that elevates the value of teaching and integrated scholarship within the traditional graduate research training environment. Launched in Fall 2021, this program was designed to be modular and easily adaptable by other disciplinary units. This paper describes the process of developing the FUSE program, details of the program structure, and data on student perceptions of the value and impact of the program on their development of pedagogical, research, and professional skills. Student feedback on positive and negative aspects of the program was also collected. Student responses to closed-ended and open-ended questions revealed positive perceived impacts on the development of a wide range of pedagogical, career, interpersonal/personal, and research skills. The majority of students reported that the program had either no impact or a positive impact on their research productivity, supporting previous work that developing teaching expertise in graduate school does not oppose disciplinary research progress. The FUSE program serves as a model for an adaptable graduate curriculum in scientific teaching and evidence-based practices that fosters the development of integrated STEM scholars and takes advantage of the pedagogical expertise of teaching-focused faculty in research-intensive universities.